SENNA Inventory for the Assessment of Social and Emotional Skills in Public School Students in Brazil: Measuring Both Identity and Self-Efficacy - Primi, Ricardo; Santos, Daniel; John, Oliver P.; De Fruyt, Filip (Frontiers in Psychology, 2021)
Responding to the need for school-based, broadly applicable, low-cost, and brief assessments of socio-emotional skills, we describe the conceptual background and empirical development of the SENNA inventory and provide new psychometric information on its internal structure. Data were obtained through a computerized survey from 50,000 Brazilian students enrolled in public school grades 6 to 12, spread across the entire State of Sao Paulo. The SENNA inventory was designed to assessing 18 particular skills (e.g., empathy, responsibility, tolerance of frustration, and social initiative), each operationalized by 9 items that represent 3 types of items: three positively keyed trait-identity items, three negatively keyed identity items, and three (always positively keyed) self-efficacy items, totaling a set of 162 items. Results show that the 18 skill constructs empirically defined a higher-order structure that we interpret as the social-emotional big five, labeled as Engaging with Others, Amity, Self-management, Emotional Regulation, and Open-mindedness. The same five factors emerged whether we assessed the 18 skills with items representing (a) a trait-identity approach that emphasizes lived skills (what do I typically do?) or (b) a self-efficacy approach that emphasizes capability (how well can I do that?). Given its target youth group is as young as 11 years old (grade 6), SENNA is also equipped to correct systematically for individual differences in acquiescence, which are shown to systematically bias results when not corrected.